Corporate Governance in Family Firms: Control Mechanisms, Agency Conflicts, and Corporate Values Across Generations - Girsang, Hardika (Simangunsong : Journal of Business Administration, Management, Economic And Accounting, 2024)
This study analyzes how control mechanisms in family firms—bothformal (board process quality: proportion of independentcommissioners, audit committee independence, intensity ofoversight agenda) and informal family-based (family constitution,family council, and succession plan)—influence agency conflict andlead to cross-generational firm value. Using a quantitative-empiricaldesign of a panel of issuers (2019–2025), this study develops twomeasurable constructs, namely the Board Process Quality Index(IKPD) and the Family Control Practices Index (IPPK), as well asagency conflict proxies (related party transaction/RPT intensity,dividend payout, and control rights–cash flow wedge). Firm value ismeasured using Tobin's Q and PBV. The relationship is testedusing fixed-effect panel regression (firm & year), mediation tests(bootstrap/SEM) and cross-generational moderation (G1, G2,G3+), complemented by robustness tests (alternative proxies,winsorizing, index redefinition). The results show that IKPD andIPPK are negatively associated with agency conflict, while wedgeincreases it. Furthermore, agency conflict is negatively associatedwith values, while IKPD is positively associated with values,confirming the mediation mechanism: control → agency conflict ↓→ values ↑. The effect of IPPK is stronger in G2/G3, indicating thatinstitutionalization of family governance becomes more crucial withtransgenerational complexity. The study's primary contributions arethe integration of formal and informal mechanisms within a single,auditable empirical framework, the differentiation of crossgenerationalheterogeneity, and the exploration of mechanisticchannels through agency conflicts. Practical implicationsemphasize strengthening board processes, institutionalizing familygovernance, and controlling wedges/RPTs to maintain and growfamily firm value across generations